(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Numerous DC–AC inverters have recently been created for solar systems. The split source inverter (SSI) is gaining popularity among them because of its one-stage functioning. This paper presents a modification of SSI’s conventional configuration (CC) into a unidirectional DC-AC configuration for better efficiency, total harmonic distortion (THD), inductor current ripple, and capacitor voltage ripple. Different control strategies have been implemented to achieve higher gain and reduced ripple and filter requirements. The MATLAB/Simulink environment is utilized for the simulation study, and the modified topology’s performance is compared with the CC-SSI. This paper proposes optimizing SSI’s inductance and capacitance network parameters to enhance gain and minimize ripple using an artificial neural network model in MATLAB. The hardware prototype is built, and the simulation results are validated.